Citizenship Learning and Democratic Engagement: Political Capital Revisited - Daniel Schugurnesky (Adult Education Research Conference, 2000)
This paper attempts to contribute to the debates on adult citizenship education, particularly regarding the connections between citizenship learning and the redistribution of political power.